2012
DOI: 10.1016/j.jfoodeng.2011.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the matrix system in the delivery and in vitro bioactivity of microencapsulated Oregano essential oil

Abstract: The effect of encapsulating matrix on retention, protection and delivery of Oregano essential oil (EO) was studied. EO was encapsulated in rice starch porous spheres, inulin and gelatine/sucrose capsules by spray drying. Gelatine/sucrose matrix was also dried by freeze drying. Experimental designs were applied to test the effect of bonding agents and solids content for rice starch and drying temperature and solids content for inulin and gelatine/sucrose systems. The ratio of gelatine/sucrose was also tested. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 45 publications
1
40
0
1
Order By: Relevance
“…However, it is certain that there is a successful retention of the core material, for all drying conditions. Besides, in previous works (Beirão da Costa et al, 2012), by confocal laser scanning microscopy, it was observed that the oil particles are located inside the capsules instead of on the surface. Changes are observed in Raman spectra at 754 cm À1 and 738 cm À1 .…”
Section: Physico-chemical Characterization Of Capsulesmentioning
confidence: 90%
See 2 more Smart Citations
“…However, it is certain that there is a successful retention of the core material, for all drying conditions. Besides, in previous works (Beirão da Costa et al, 2012), by confocal laser scanning microscopy, it was observed that the oil particles are located inside the capsules instead of on the surface. Changes are observed in Raman spectra at 754 cm À1 and 738 cm À1 .…”
Section: Physico-chemical Characterization Of Capsulesmentioning
confidence: 90%
“…In order to assess the transport properties of EO entrapped in inulin microparticles, mathematical models were used to describe the physical mechanism. Several authors have proposed mathematical relationships to describe compound release from microcapsules (Prata, Zanin, Ré, & Grosso, 2008;Romero-Cano & Vincent, 2002;Zhang, Grijpma, & Feijen, 2006), assuming some restrictions for polymeric matrices as described in a previous work (Beirão da Costa et al, 2012). Based on these works, a linear superimposition model was applied which describes the release of EO from spherical microparticles at time t by well-known equations:…”
Section: Release Of Eo From Microcapsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the WM should have a tendency to form a fine and dense network during drying, and should not permit a lipid separation from the emulsion during dehydration (Gharsallaoui and others ; Calvo and others ). The spray‐drying process has been used to encapsulate extracts of Ilex paraguariensis (Nunes and others ), Capsicum annuum L. (Guadarrama‐Lezama and others ), Opuntia ficus‐indica (Saenz and others ), black currant polyphenols (Bakowska‐Barczak and Kolodziejczyk ), Averrhoa carambola (Saikia Mahnot and Mahanta ), clove (Chatterjee and Bhattacharjee ), pomegranate peel (Çam Içyer and Erdoǧan ), fish oil, olive, chia, and flax oils (Polavarapu and others ; Quispe‐Condori and others ; González and others ), rosemary EO (De Barros Fernandes and others ), Schinus molle L. (López and others ), oregano, citronella and marjoram EOs (Baranauskienė and others ; Beirão Da Costa and others ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation is one of the most effective methods to reduce irritancy and losses by evaporation (5). In this method, the wall-forming polymer plays an important role as it is responsible for the protection of the encapsulated essential oil (6). Therefore, chitosan, a natural cationic linear polysaccharide composed of randomly distributed β-(1-4)-linked D-glucosamine (deactylated unit) and N-acetyl-D-glucosamine (acetylated unit), was selected as it is widely used in topical dressing due to haemostatic and healing potential.…”
Section: Introductionmentioning
confidence: 99%